Synthesis and Characterization of a Novel Composite Scaffold Based on Hyaluronic Acid and Equine Type I Collagen - Erwin Pavel Lamparelli; Veronica Casagranda; Daniele Pressato; Nicola Maffulli; Giovanna Della Porta; Davide Bellini (MDPI AG, 2022)
Herein, the synthesis and characterization of a novel composite biopolymer scaffold-based on equine type I collagen and hyaluronic acid-were described by using a reaction in heterogeneous phase. The resulting biomimetic structure was characterized in terms of chemical, physical, and cytotoxicity properties using human-derived lymphocytes and chondrocytes. Firstly, FT-IR data proved a successful reticulation of hyaluronic acid within collagen structure with the appearance of a new peak at a wavenumber of 1735 cm−1 associated with ester carbonyl stretch. TGA and DSC characterizations confirmed different thermal stability of cross-linked scaffolds while morphological analysis by scanning electron microscopy (SEM) suggested the presence of a highly porous structure with open and interconnected void areas suitable for hosting cells. The enzymatic degradation profile confirmed scaffold higher endurance with collagenase as compared with collagen alone. However, it was particularly interesting that the mechanical behavior of the composite scaffold showed an excellent shape memory, especially when it was hydrated, with an improved Young's modulus of 9.96 ± 0.53 kPa (p ≤ 0.001) as well as a maximum load at 97.36 ± 3.58 kPa compared to the simple collagen scaffold that had a modulus of 1.57 ± 0.08 kPa and a maximum load of 36.91 ± 0.24 kPa. Finally, in vitro cytotoxicity confirmed good product safety with human lymphocytes (viability of 81.92 ± 1.9 and 76.37 ± 1.2 after 24 and 48 h, respectively), whereas excellent gene expression profiles of chondrocytes with a significant upregulation of SOX9 and ACAN after 10 days of culture indicated our scaffold's ability of preserving chondrogenic phenotype. The described material could be considered a potential tool to be implanted in patients with cartilage defects.